Leader-managers in the public sector managing for results - Dukakis, Michael S. (Michael Stanley) 1933-; Portz, John 1953- (Abingdon, Oxon [England] Routledge, 2015)
"At a time of doubt and concern about government and its capacity to serve the public, this book highlights the critical skills and practices that characterize good leadership and good management" "Authors Michael S. Dukakis and John Portz distilled this list from in-depth interviews with seven successful leader-managers in different policy fields and at different levels of the federal system. In the first part of the book they present these common skills using extensive analysis of the interviews, and in the second part they provide the actual interview transcripts. Readers can start with a focus on the detailed presentation of the key skills and practices, then turn to the transcripts to explore in more depth the experiences of these successful leader-managers."
1. Leading and Managing in the Public Sector: The Leader-Manager -- 2. Introducing Our Leader-Managers -- 3. Picking and Motivating Your People -- 4. Walking Around... Listening... Learning -- 5. Fostering Collaboration and Support -- 6. Building Effective Organizations -- 7. Communicating With the Public -- 8. Demonstrating Character and Integrity -- 9. Conclusion -- Interview Transcripts -- Kimberly Belshe-Secretary, California Health and Human Services Agency -- John B. Catoe Jr.-General Manager, Washington Metropolitan Area Transit Authority -- Thomas W. Payzant-Superintendent, Boston Public Schools -- Federico Fabian Pena-Mayor, Denver, Colorado; Secretary, U.S. Department of Transportation -- Mary E. Peters-Director, Arizona Department of Transportation; Secretary, U.S. Department of Transportation -- Jean Hoefer Toal-Chief Justice, South Carolina Supreme Court -- Bernard E. Trainor-Lieutenant General, U.S. Marine Corps.
Includes bibliographical references (pages 201-202) and index.
Keywords: Leadership -- United States; Government executives -- United States; Organizational effectiveness -- United States